Distant metastases in ovarian carcinoma. Issue 2 (1st February 2003) - Cormio, G.; Rossi, C.; Cazzolla, A.; Resta, L.; Loverro, G.; Greco, P.; Selvaggi, L.
Abstract : Distant metastases are unusual at presentation and during the course of ovarian carcinoma. The aim of the present study was to determine the incidence and prognostic factors of distant metastases consistent with stage IV disease in ovarian cancer patients. A retrospective chart review was conducted on 162 patients with epithelial ovarian carcinoma treated at our Unit between 1991 and 2000. Pertinent clinical information, pathologic data, treatment, and prognostic factors for survival following documentation of distant metastatic disease were collected. The significance of the association between metastatic status and various clinical variables was assessed using the standard chi-square test. Survival time was calculated from the time of diagnosis of ovarian cancer and from the time of diagnosis of the distant metastases. A logistic regression procedure was used to estimate the odds of metastatic status given the presence of certain clinical variables. A total of 67 metastatic sites were diagnosed in 50 patients. Thirteen patients (8%) had distant metastatic disease at the time of diagnosis, 37 patients (22%) had distant metastases at the time of recurrent of progressive disease. Site of metastases were: liver, 21; pleura, 11; lung, 8; central nervous system and skin, 7 each; extra-abdominal lymph nodes and spleen, 5 each; bone, 2; and breast, 1. Significant risk factors for the development of distant metastases were stage, grade, and lymph node involvement. Median interval time between diagnosis of ovarian cancer and documentation of metastatic disease was 44 months (range 3–105), and at the time of diagnosis of distant disease, 36 of 50 patients (72%) had other sites of disease (intra-abdominal or extra-abdominal). Median survival from diagnosis of distant disease was 12 months (range 1–58). In univariate analysis performance status ( P = 0.03 ), the presence of other sites of disease ( P = 0.04 ) and interval time between diagnosis of ovarian cancer and documentation of distant metases ( P = 0.03 ) were the only factors significantly associated with survival. Long interval time remained significant for prognosis in multivariate analysis also ( P = 0.04 ). Distant metastasis consistent with stage IV disease is a late complication that occurs in about one third of ovarian cancer patients. Prognosis after documentation of distant metastases is poor. We conclude the most important prognostic factor associated with survival is the interval time between diagnosis of ovarian cancer and documentation of distant metastases.